Dermatoglyphic characteristics of elite level female skaters according to competition mode (2024)
Dermatoglyphics is presented as a method that allows understanding the relationship between the patterns established in the fingerprints of human beings and the physical abilities in the various sports modalities. The present work analyzed the dermatoglyphic characteristics of skaters of world elite level according to the competition modality. Skaters specialized in speed events (n=10) and endur-ance events (n=10) were evaluated (n=20). The protocol proposed by Cummins and Midlo was used for dermatoglyphic analysis. The results showed that there are significant differences (p>0.05) between competition modalities for the variables Delta (D10), whorls (W) and total line count (SQTL), as for the competition specialty; the speed modality presented an increase in the levels of arches (A) and loops (L) and decrease in the total line count (SQTL), as for the endurance presented an increase in the levels of (L), (W), (SQTL) and decrease (A). High-achieving sports develop elite athletes through constant selection and long-term directed training, which in the results of the present study orient the athlete's profile, concluding that the dermatoglyphic characteristics D10, SQTL and W differ between competition modalities, being higher in endurance skaters than in sprinters. Therefore, in the present work it was found that dermatoglyphics vary for the competitive specialty in the high-level skaters evaluated.